Glass ionomer cement: Clinical applications (Research, Society and Development, 2024)
This study carried out a literature review, as an exploratory and descriptive method, with a qualitative approach, based on the analysis of the content of articles from scientific journals. Objective: to carry out a literature review in order to promote the applicability of Glass Ionomer Foundation in dentistry, providing greater knowledge to surgeons-dentists about this material. The inclusion criteria defined for the selection of two articles are: full texts available; In the period from 2019 to 2023. Foram found 08 studies, we will collaborate to the results and discuss. It was observed that the Glass Ionomer Foundations have importance not to mention respect for their insertability in dentistry, they present biocompatible properties like the dental elements, thus enabling from their manual at the same time their insertion in the cavities, in addition to presenting a favorable clinical effectiveness in the procedures. Clinics Correct manipulation, indication and application are intrinsically related to proper clinical performance and its properties. Among the properties of Glass Ionomer Foundations, the addition to mineralized textiles, mechanical resistance, coefficient of linear thermal expansion similar to dental structure, bioactivity, biocompatibility, fluoride release and oil aesthetics stand out. Thus, the clinical recommendations for the use of Glass Ionomer Foundations are broad in dentistry.